2008
DOI: 10.1124/jpet.107.135186
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Effect of Sodium 4-Phenylbutyrate in ΔF508-Cystic Fibrosis Transmembrane Conductance Regulator Lung Epithelial Cells: Involvement of Extracellular Signal-Regulated Protein Kinase 1/2 and c-Jun-NH2-Terminal Kinase Signaling

Abstract: Sodium

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
(56 reference statements)
1
22
0
Order By: Relevance
“…Interestingly, earlier studies investigating the effects of butyrate and its derivative 4-phenylbutyrate on pharmacological rescue of F508del-CFTR found, in line with our results, that 4-phenylbutyrate (at 6-10 mM) had a pro-inflammatory effect on CFBE cells (CFBE41o-, also used in this study, and IB3-1 cells) by upregulating IL-8 [25,26]. However, in our study there was no correlation between SCFA concentrations at the time of pulmonary exacerbation with IL-8 or the change in IL-8 after antibiotic treatment, and no correlation between the change in SCFA concentrations before and after antibiotic treatment with either the change in IL-8 or the levels of IL-8 after antibiotic treatment, illustrating that SCFAs may contribute to but are not the major factor affecting individual IL-8 levels.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Interestingly, earlier studies investigating the effects of butyrate and its derivative 4-phenylbutyrate on pharmacological rescue of F508del-CFTR found, in line with our results, that 4-phenylbutyrate (at 6-10 mM) had a pro-inflammatory effect on CFBE cells (CFBE41o-, also used in this study, and IB3-1 cells) by upregulating IL-8 [25,26]. However, in our study there was no correlation between SCFA concentrations at the time of pulmonary exacerbation with IL-8 or the change in IL-8 after antibiotic treatment, and no correlation between the change in SCFA concentrations before and after antibiotic treatment with either the change in IL-8 or the levels of IL-8 after antibiotic treatment, illustrating that SCFAs may contribute to but are not the major factor affecting individual IL-8 levels.…”
Section: Discussionsupporting
confidence: 79%
“…In contrast, high concentrations markedly abrogated iNOS expression in A549 as well as primary control and cystic fibrosis epithelial cells. While it is not clear whether the effect on iNOS expression was direct or mediated by changes in the inflammatory response, SCFAs and their derivatives have previously been shown to directly inhibit activation of nuclear factor-κB, a key regulator of iNOS transcription [26,36]. The presence of SCFAs in airways may contribute to the dysregulation of NOS in cystic fibrosis airways, which is supported by our observation that lower concentrations of these bacterial metabolites in sputum of cystic fibrosis patients were predictive for the increase in airway NO after antibiotic therapy in our small cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of cells with other inducers of HDACi in vitro (such as trichostatin A) was shown to modulate IL-8 production in both an NFkB-dependent and AP-1-dependent fashion, but this effect is highly cell-specific (33,45). In addition, Roque and colleagues observed that 4-PBA enhances the production of IL-8 in lung epithelial cells expressing DF508-CFTR (44). The treatment of these cystic fibrosis cell lines with 4-PBA resulted in an activation of intracellular JNK signaling and the release of IL-8, despite a decrease in NFkB activation, a result similar to what we observed here in cells expressing BRICHOS mutants (Figures 7, 8, and E4).…”
Section: Discussionmentioning
confidence: 97%
“…Mechanistically, the lack of an antiinflammatory effect of 4-PBA in our model system may have been attributable to off-target effects of 4-PBA, as described in other systems. These effects include histone deactylase inhibition (HDACi) (41)(42)(43) and enhanced MAPK (JNK) signaling (44). The treatment of cells with other inducers of HDACi in vitro (such as trichostatin A) was shown to modulate IL-8 production in both an NFkB-dependent and AP-1-dependent fashion, but this effect is highly cell-specific (33,45).…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK family of serine-threonine protein kinases is a highly conserved family consisting of three primary members; extracellular signal-related kinases (ERK), c-Jun amino-terminal kinases (JNK), and p38. MAPKs play an active signaling role following multiple stimuli, some of which include irradiation, osmotic stress, inflammation, growth factors, and mechanical loading (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%